B7-H7 knockdown suppresses the proliferation, metastasis, and drug resistance of B-cell non-Hodgkin lymphoma cells by inhibiting the PI3K/Akt pathway - Zhai, Aili; Zou, Qing; Yin, Jiawei; Ge, Shixin; Xiong, Xingfang; Yan, Tao; Xie, Xiaoli; Wang, Lijuan (Frontiers in Oncology, 2025)
BackgroundThe activation of key immune regulatory factors is an important driving factor in the progression of therapeutic resistance in patients with B-NHL. As a novel immune regulatory factor of the B7 family, surface B7-H7 interacts with receptors on active T cells to promote tumor immune escape. However, investigations of B7-H7 on B-NHL are still lacking.MethodsIn vitro assays were performed to examine the proliferation, migration, invasion, and starvation tolerance abilities of B7-H7 knockdown cells. A xenograft mouse model of B-NHL was established to investigate the in vivo functions of B7-H7. The impact of B7-H7 on patient prognosis was analyzed using the GEPIA and GEO datasets. We also examined whether B7-H7 knockdown affects resistance to rituximab (RTX) and verified this by establishing a rituximab-resistant cell line (RRC). Finally, RNA sequencing was performed on B7-H7 knockdown cells, rituximab-treated cells, and rituximab-resistant cells.ResultsB7-H7 knockdown inhibited tumor growth in vivo and suppressed cell proliferation, migration, invasion, and starvation-bearing ability in vitro. Patients with diffuse large B-cell lymphoma (DLBCL) with high expression of B7-H7 showed an increased death rate. B7-H7 knockdown increased sensitivity to rituximab, and the strong resistance of RRC was weakened to some extent when B7-H7 expression in RRC was inhibited. RNA sequencing revealed that the PI3K/Akt pathway may play an important role in B7-H7 knockdown in cells and drug-resistant strains. This was confirmed by western blotting and agonist/inhibitor treatment.ConclusionsSuppression of B7-H7 inhibited tumor progression and induced RTX sensitivity by suppressing the PI3K/Akt pathway.